2016
DOI: 10.1136/oemed-2015-103489
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' attentional performance following a 24-hour observation period: do we need to regulate sleep prior to work?

Abstract: Our study suggests that baseline sleep before 24 hours of observation impacts the accuracy of physicians' attentional testing at 24 hours. Further study is required to determine if optimising physician sleep prior to overnight call shifts is a sustainable strategy to mitigate the effects of sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
3
1
Order By: Relevance
“…[ 14 ] Prior studies have demonstrated that sleeping impairment decreased concentration and increased burnout. [ 15 , 16 ] However, in contrast to previous research, our study did not find an association between sleep time with burnout. [ 17 ] Considering the fact that our data regarding sleep time and sleep quality were all self-reported, the definite relationship between sleep and burnout in residents in SRT should be explored in future study through sleep monitoring.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 14 ] Prior studies have demonstrated that sleeping impairment decreased concentration and increased burnout. [ 15 , 16 ] However, in contrast to previous research, our study did not find an association between sleep time with burnout. [ 17 ] Considering the fact that our data regarding sleep time and sleep quality were all self-reported, the definite relationship between sleep and burnout in residents in SRT should be explored in future study through sleep monitoring.…”
Section: Discussioncontrasting
confidence: 99%
“…Sleep impairment is linked not only to poor health outcomes such as obesity 2,3 and cardiovascular disease 4 but also to decreased task performance and concentration. 5 Prior studies of medical residents identified associations between impaired sleep and both medical errors and burnout, including increased depression and anxiety. [6][7][8] Other research has illustrated that work hour changes may not lead to greater sleep or to better clinical performance [9][10][11][12] and that factors other than clinical work hours may contribute to fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…1 Sleep loss has been linked to performance decrements from reduced response time, reduced learning, decreased short-term recall of working memory, micro-sleeps, and increased commission and omission errors, 10 as well as increased accidents and errors 3,9 . For example, Smyth et al 26 found extended wakefulness from physician overnight shifts led to decrements in attentional accuracy and Lo et al 20 found restricted sleep led to decrements in sustained attention, speed of processing, and subjective alertness. Maquet et al 21 observed that regional brain activity during rapid-eye-movement (REM) sleep is influenced by training on a task, highlighting that procedural memories are processed during REM sleep.…”
Section: Introductionmentioning
confidence: 99%